Preparation of porous PtAuCu@Pt core-shell catalyst for application to oxygen reduction - Sohn, Yeonsun; Jung, Namgee; Lee, Myeong Jae; Lee, Soohyung; Nahm, Kee Suk; Kim, Pil; Yoo, Sung Jong (한국공업화학회, 2019)
Designing a Pt-based catalyst with high oxygen reduction reaction (ORR) performance is very important for the improvement of the economic feasibility of polymer electrolyte fuel cells. Herein, we suggest a method to prepare a Pt-based core-shell catalyst with high ORR activity and durability by galvanic displacement between Cu on a thermally annealed sample of (PtxAuy)(1)Cu-5/C-HT and Pt ions. The resultant catalysts ((PtxAuy)(1)Cu-5@Pt/C) showed a porous core-shell structure with a Pt-enriched surface. The composition of (PtxAuy)(1)Cu-5/C-HT influenced the physical properties of the resultant (PtxAuy)(1)Cu-5@Pt/C catalysts. (PtxAuy)(1)Cu-5@Pt/C catalysts exhibited better ORR performance than a commercial Pt/C one and their performance varied with the composition. Among the catalysts examined, (Pt1Au0.1)@Pt/C showed the best ORR activity. Specifically, it delivered a mass and specific activity of 0.660 mA/mg(PGM) cm(2) and 1506.2 mA/cm(pt)(2) at 0.9 V (vs. RHE), respectively. These are 2.7 and 4.2 times higher than corresponding values obtained for Pt/C. In an accelerated degradation test, addition of Au proved beneficial for the design of a highly durable catalyst. The effect of the Au content on the physical properties and ORR performance of catalysts was interpreted in detail. (C) 2019 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.